Personality Types and L2 Reading: correlation between University Students MBTI Profiles and Reading Proficiency - Medjedel, Khaoula (Technium Social Sciences Journal, 2021)
Personality types have a considerable impact on our understanding of the outer world, perception and energy. Personality influence on language learning and proficiency, however, is controversial. This study demonstrates the relationship between the Myers-Briggs Type Indicator (MBTI) profiles and L2 reading proficiency of L1 Arab undergraduates. First, learners’ reading proficiency levels were associated with their Introversion/Extraversion preferences. Then, function pairs of both introverts and extraverts that contributes to the highest score of L2 reading proficiency were determined. As most reading tests are based on choice, it is very logical to consider the MBTI function pairs as they represent the mental functions used for decision-making and information gathering. Fifty (50) Arab male students from the College of Business Administration (Saudi Arabia) were randomly selected. Two instruments were used to collect data; MBTI as a personality instrument, and TOEIC Bridge as a reading test. Findings showed a lack of statistically significant relationship between Introversion/Extraversion and L2 reading proficiency. Yet, Intuitive personalities (NT/NF) preferences achieved higher scores in the TOEIC Bridge compared to their counterparts of the Sensing personalities (ST/SF). Personality types have undoubted influence on our lifestyle and attitudes. Yet, considering personality as a weighty factor in language learning and proficiency is still debatable.